Optimalisasi Keuangan UMKM Batako Simbah Melalui Penerapan Laporan Sederhana Dan Digitalisasi Excel - Fiqih Kirana Dwi Murti; Rosati Wahdana; Sumaryanto (LPPI UMN AL WASHLIYAH, 2025)
MSMEs contribute significantly to the growth of the national economy, although many still face challenges in managing their finances in an orderly and structured manner. Batako Simbah MSME is one example of a business actor that has not yet implemented an adequate financial recording system. This activity aims to optimize financial management through training in basic financial reporting and digitalization using Microsoft Excel. The methods used include observation, material presentation, technical training, and intensive mentoring. The results show that business owners have begun to understand the importance of financial recording, are able to prepare income statements, and calculate the cost of goods manufactured independently. The use of Excel for digital financial records has proven to improve the efficiency, accuracy, and accountability of financial information. This activity is expected to be the first step toward more professional financial management practices within MSMEs, with a long-term focus on sustainability.